1986
DOI: 10.1246/bcsj.59.73
|View full text |Cite
|
Sign up to set email alerts
|

Geometrical Isomerism of Phenylhydrazones of α-Keto Esters. II. p-Substituted Phenylhydrazones of Ethyl Pyruvate and 2,4-Dinitrophenylhydrazones of Some α-Keto Esters

Abstract: Each geometrical isomer of various substituted phenylhydrazones of ethyl pyruvate and 2,4-dinitrophenylhydrazones of some α-keto esters was isolated in a pure state. Partial isomerizations of the E-isomers of the former hydrazones to the Z-isomers took place by keeping solutions of the hydrazones in organic solvents containing C, H, and Cl in the dark. An E- or Z-structure was assigned to each molecule on the basis of IR and 1H NMR spectra. In all cases, isomers with higher Rf-values on a silica gel TLC (using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1987
1987
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…To our expectation, the desired coupling product 3a was obtained in 82% yield within 2 h (entry 1). From the downfield chemical shift of the N–H proton, 3a should have a Z-configuration . Other solvents such as dimethylformamide (DMF), CH 3 CN, CH 3 NO 2 , CHCl 3 , and 1,2-ClCH 2 CH 2 Cl (DCE) were also investigated (entries 2–6).…”
Section: Resultsmentioning
confidence: 51%
See 1 more Smart Citation
“…To our expectation, the desired coupling product 3a was obtained in 82% yield within 2 h (entry 1). From the downfield chemical shift of the N–H proton, 3a should have a Z-configuration . Other solvents such as dimethylformamide (DMF), CH 3 CN, CH 3 NO 2 , CHCl 3 , and 1,2-ClCH 2 CH 2 Cl (DCE) were also investigated (entries 2–6).…”
Section: Resultsmentioning
confidence: 51%
“…From the downfield chemical shift of the N−H proton, 3a should have a Zconfiguration. 12 Other solvents such as dimethylformamide (DMF), CH 3 CN, CH 3 NO 2 , CHCl 3 , and 1,2-ClCH 2 CH 2 Cl (DCE) were also investigated (entries 2−6). Both DCE and CH 2 Cl 2 were found to be the most suitable.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Control experiments were conducted (Table S2b, c) 38 that confirmed that heating alone was sufficient for the reaction to be initiated and proceed to completion. However, it must be noted that upon scale-up TSE is likely to be advantageous as it provides a means of intimately mixing the substrates as well as an even distribution of heat transfer.…”
Section: ■ Results and Discussionmentioning
confidence: 99%